Blue Mussels (Mytilus edulis) Improve Light Conditions in a Downstream Eelgrass (Zostera marina) Meadow in the Limfjorden, Denmark - Emil Hoffmann Bohr; Daniel Taylor; Tobias Kuhlmann Andersen; Aris Thomasberger; Mollie Elizabeth Brooks; Line Hermannsen; Karen Timmermann (Estuaries and Coasts, 2026)
Eelgrass ( Zostera marina ) constitutes critical habitat worldwide in terms of ecosystem services and biodiversity, yet less than 30% coverage remains in Danish waters compared to historical records. Persistent eutrophication has substantially reduced water clarity, making light the primary limiting factor for the distribution of eelgrass. Through particle filtration, filter-feeders such as blue mussels ( Mytilus edulis ) can influence light conditions in coastal habitats. This study hypothesized that blue mussel beds could improve light conditions within nearby eelgrass meadows and thus facilitate eelgrass growth. Light and current data were gathered from 37 sampling stations in three different habitats (eelgrass meadows, blue mussel beds, and mixed) at two sites in a shallow estuary in the Limfjorden, Denmark, characterized by different mussel–eelgrass configurations from May to September 2023. Across the three habitats, the light attenuation coefficient for photosynthetically active radiation, K d (PAR), was generally lower above blue mussel beds compared to eelgrass meadows and mixed habitats, likely due to suspended particle filtration by the mussels. Further supporting that mussels improved light conditions, median K d (PAR) in the eelgrass was lower when the eelgrass meadows were downstream from the mussel beds, than for the opposite current direction. Using state-space models, temporal changes in K d (PAR) were shown to be predominantly controlled by seasonal changes in chlorophyll a concentration in Lovns Broad, whereas current velocity only had minor impact. These findings suggest that blue mussels can improve water clarity in adjacent eelgrass meadows, likely alleviating light limitation and thereby supporting eelgrass growth and ecosystem functioning.

Comparing tree swallow dispersal strategies in a continuous mainland environment - Kelly K. Hallinger; Teresa M. Pegan; Michael J. Andersen; Daniel R. Ardia; Amos Belmaker; David Chang van Oordt; Valentina Ferretti; Anna M. Forsman; Jennifer R. Gaul; Paulo E. Llambías; Sophia C. Orzechowski; J. Ryan Shipley; et al. (Ecology, 2026)
Dispersal is one of the most important aspects of animal behavior and can have far‐reaching consequences for organismal ecology and evolution. Despite recent theoretical advances in understanding why individuals within the same population vary in dispersal behavior, relatively few studies have empirically evaluated the long‐term causes and consequences of variable dispersal within natural populations. In this study, we used life history data collected over the course of 16 years to examine fitness outcomes in 867 known‐age female tree swallows breeding in New York, USA, that differed in their dispersal status: “immigrant” females, defined as dispersers that hatched elsewhere, and “local” females, defined as non‐dispersers that hatched within the study site and returned there after migration to breed. We also compared the life history responses of immigrant and local females to natural variation in weather, nest predation risk, and social environment at their breeding site. Local females were more likely to produce fledglings that recruited into the study area as adults. We also found several instances in which dispersal status interacted with an environmental metric to influence relative fitness, and these responses were largely consistent across life history measures. Overall, immigrant females were relatively resilient to variation in their extrinsic environment, while local females were highly sensitive to environmental conditions at the breeding site, performing relatively well when conditions were benign and faring relatively poorly as conditions became more stressful. We found little evidence that distance dispersed within a study site impacted female fitness, suggesting that the dispersal‐associated differences in fitness that we observed operate mostly across broader spatial scales. Future work should undertake the direct and simultaneous measurement of behavior, physiology, and fitness of immigrant and local females across environmental contexts and should seek to understand whether and how context‐dependent fitness variation of dispersers and non‐dispersers scales up to influence larger ecological and evolutionary processes.

Redfield revisited: Insights into freshwater seston carbon : nitrogen : phosphorus stoichiometry - Isabelle M. Andersen; Jason M. Taylor; Daniel Graeber; Patrick T. Kelly; Alexa K. Hoke; Caleb J. Robbins; J. Thad Scott (Limnology and Oceanography, 2025)
Seston carbon (C), nitrogen (N), and phosphorus (P) stoichiometry plays a fundamental role in aquatic ecosystems, influencing nutrient cycling, primary and secondary production, and trophic interactions. In freshwater systems such as lakes, P limitation is more common, whereas in marine environments, N more frequently limits primary production, reflecting different nutrient limitation patterns across aquatic ecosystems. The Redfield ratio (C 106 : N 16 : P 1 molar), developed from marine seston, has long been considered a benchmark for nutrient composition and a predictor of nutrient limitation across aquatic ecosystems. A later global freshwater and marine seston survey proposed the Sterner ratio (C 166 : N 20 : P 1 molar) as a broader global seston average. We present the results of a fully replicated, multi‐annual freshwater mesocosm experiment testing the effect of variable resource N : P stoichiometry on seston stoichiometry. We found that the seston C : N : P ratio aligned with the Redfield ratio under N‐limited conditions, while P‐limited conditions aligned with the Sterner global survey of freshwater ecosystems. Ternary plots offered visual insight into stoichiometric shifts, showing a trend toward P depletion relative to C and N as N : P supply increases. The average seston C : N : P ratio observed from our experimental data was C 141 : N 22 : P 1 (molar) and variation in seston C : N : P was small compared to the resource ratio gradient. Our mesocosm experiment showed that the Redfield ratio provides a useful description of seston stoichiometry in N‐limited freshwater ecosystems. These findings advance the understanding of bottom‐up controls on seston C : N : P stoichiometry and highlight the need to refine ecological theories regarding the application of the Redfield ratio in freshwater ecosystems.

Back-shore vegetation as trap for marine plastic pollution, Dar es Salaam, Tanzania - Frederik Oksbjerg Mikkelsen; Thorbjørn Joest Andersen; Christine Ørsted; Amanda Bojer; Desderius Msafiri; Stanley D. Katega; Martine M. Kabezi; Flora Idan Mwasamila; Dativa J. Shilla; Daniel Shilla; Marianne Nylandsted Larsen; Mikkel Fruergaard (Marine Pollution Bulletin, 2025)

In situ approaches to marine and terrestrial metabolomics - Daniel Jordan Otto; Morgane Mauduit; Scott A. Jarmusch; Ling Ding; Aaron John Christian Andersen (Phytochemistry Letters, 2025)

Assessing the timing of deep ocean oxygenation from uranium elemental and isotopic compositions of ophiolites - Joel B. Rodney; Morten B. Andersen; Daniel Stubbs; C. Johan Lissenberg; Omar Gianola; Matthias Willbold; Tim Elliott (Earth and Planetary Science Letters, 2025)

A mixed-method approach to understand energy-related occupant behavior and everyday practices in multi-story residential buildings - Kamilla Heimar Andersen; Anders Rhiger Hansen; Anna Marszal-Pomianowska; Henrik N. Knudsen; Daniel Leiria; Per Kvols Heiselberg (Energy and Buildings, 2025)

Which Body Size Metrics Should Be Used for Assessing Temperature Impacts on Fish Growth and Size? - Asta Audzijonyte; Ken H. Andersen; David Atkinson; Jennifer S. Bigman; Julia L. Blanchard; Amy R. Coghlan; Freddie Heather; Max Lindmark; John R. Morrongiello; Daniel Pauly (Global Change Biology, 2025)
An extensive literature and debate exist on how and why temperature impacts animal, and especially ectotherm, body sizes. However, there remain considerable discrepancies and misunderstandings in the key definitions and concepts of body size used to describe observed temperature impacts across studies. For fish and other animals that continue growing throughout life, body size can be defined as size‐at‐maturity, adult size, asymptotic size, maximum observed size, population‐averaged length or mass, or average size‐at‐(arbitrary)‐age. These concepts of size are not equivalent, and temperature is likely to affect each in different ways. Some disagreement about temperature impacts on fish body sizes might relate to the different body size and growth metrics used, especially when combined with different biological scales (individual, population, or community) and empirical contexts (laboratory, field). Here, we review six common confusions associated with the measurement of “size” in fish and other water‐breathing ectotherms and recommend consistent and accurate use of terms and methodology to ensure that studies of global warming impacts on fish sizes can be compared and interpreted unequivocally.

Policy and pricing tools to incentivize distributed electric vehicle-to-grid charging control - Daniel Andersen; Siobhan Powell (Energy Policy, 2025)

Irrigation and oil palm empty fruit bunch mulch enhance eggplant growth, radiation interception and dry matter yield - John Bright Amoah Nyasapoh; Eric Oppong Danso; Daniel Selorm Kpodo; William Amponsah; Emmanuel Arthur; Edward Benjamin Sabi; Peter Bilson Obour; William Akortey; Bernard Kwabena Boadi Mensah; Grace Elorm Ayayi; Mathias Neumann Andersen (European Journal of Agronomy, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

CON-SST-RAIN: Continuous Stochastic Space–Time Rainfall generation based on Markov chains and transposition of weather radar data - Christoffer B. Andersen; Daniel B. Wright; Søren Thorndahl (Journal of Hydrology, 2024)

Assessing biochar and zeolite for enhanced agricultural sustainability of swine manure - Krishna Yadav; Santanu Bakshi; Chumki Banik; Daniel S. Andersen; Robert C. Brown (Journal of Environmental Chemical Engineering, 2024)

Effects of swine manure dilution with lagoon effluent on microbial communities and odor formation in pit recharge systems - Okhwa Hwang; Bryan Emmett; Daniel Andersen; Adina Howe; Kyoung Ro; Steven Trabue (Journal of Environmental Management, 2024)

Biomass and trait biogeography of cephalopods on the European and North American continental shelves - Daniel Ottmann; Ken H. Andersen; P. Daniël van Denderen (Global Ecology and Biogeography, 2024)
Aim We evaluate whether the biomass and trait biogeography of cephalopods follow the distribution expected by metabolic theory for ectotherms with rapid growth and high metabolic rate. Location Continental shelves of the North Atlantic and Northeast Pacific oceans; global marine ecoregions. Time Period 1968–2020. Major Taxa Studied Cephalopods and fishes (Chondrichthyes and Osteichthyes). Methods We map the biomass of cephalopods and their traits across marine shelves using scientific bottom trawl survey data from the North Atlantic and Northeast Pacific. We further map global fisheries catch. We apply statistical methods to evaluate how temperature, zooplankton productivity and depth drive these patterns. Results Cephalopods represent a small fraction (1%) of the combined fish and cephalopod biomass on continental shelves. However, their distribution displays a high regional heterogeneity, with some areas being virtually absent of cephalopods and other areas accounting for up to 24% of total biomass. Higher temperatures and zooplankton productivity are associated with increased cephalopod biomass and proportional biomass relative to fish. The largest cephalopods are found in the Northeast Pacific. Growth rates are highest in warmer waters with fastest growth rates found in lower latitudes of the North Atlantic. Cephalopods constitute 5% of the combined fish and cephalopod global fisheries catch. This proportion varies across regions. Higher temperature and zooplankton productivity are associated with increased cephalopod catch relative to fish. Main Conclusions Temperature and productivity shape the large‐scale biogeography of cephalopods and their traits on marine shelves. The relations with temperature suggest that future warming could lead to a proliferation of fast‐growing cephalopods in cold and temperate systems, with implications for ecosystem dynamics and fisheries. Despite a relatively low observed biomass, cephalopods hold substantial potential to change ecosystem structure and functioning given their high energy lifestyle.

Ecological network structure in response to community assembly processes over evolutionary time - Natalie R. Graham; Henrik Krehenwinkel; Jun Ying Lim; Phillip Staniczenko; Jackson Callaghan; Jeremy C. Andersen; Daniel S. Gruner; Rosemary G. Gillespie (Molecular Ecology, 2023)
The dynamic structure of ecological communities results from interactions among taxa that change with shifts in species composition in space and time. However, our ability to study the interplay of ecological and evolutionary processes on community assembly remains relatively unexplored due to the difficulty of measuring community structure over long temporal scales. Here, we made use of a geological chronosequence across the Hawaiian Islands, representing 50 years to 4.15 million years of ecosystem development, to sample 11 communities of arthropods and their associated plant taxa using semiquantitative DNA metabarcoding. We then examined how ecological communities changed with community age by calculating quantitative network statistics for bipartite networks of arthropod–plant associations. The average number of interactions per species (linkage density), ratio of plant to arthropod species (vulnerability) and uniformity of energy flow (interaction evenness) increased significantly in concert with community age. The index of specialization has a curvilinear relationship with community age. Our analyses suggest that younger communities are characterized by fewer but stronger interactions, while biotic associations become more even and diverse as communities mature. These shifts in structure became especially prominent on East Maui (~0.5 million years old) and older volcanos, after enough time had elapsed for adaptation and specialization to act on populations in situ. Such natural progression of specialization during community assembly is probably impeded by the rapid infiltration of non‐native species, with special risk to younger or more recently disturbed communities that are composed of fewer specialized relationships.

Where the water goes: Partitioning surface flow and streambed infiltration in an ephemeral river laboratory experiment - Daniel Partington; Margaret Shanafield; Eddie W. Banks; Martin S. Andersen; Gabriel C. Rau; Stefan Felder; Craig T. Simmons (Journal of Hydrology, 2023)

Demersal fish biomass declines with temperature across productive shelf seas - Daniel van Denderen; Aurore A. Maureaud; Ken H. Andersen; Sarah Gaichas; Martin Lindegren; Colleen M. Petrik; Charles A. Stock; Jeremy Collie (Global Ecology and Biogeography, 2023)
Aim Theory predicts fish community biomass to decline with increasing temperature due to higher metabolic losses resulting in less efficient energy transfer in warm‐water food webs. However, whether these metabolic predictions explain observed macroecological patterns in fish community biomass is virtually unknown. Here, we test these predictions by examining the variation in demersal fish biomass across productive shelf regions. Location Twenty one continental shelf regions in the North Atlantic and Northeast Pacific. Time Period 1980–2015. Major Taxa Studied Marine teleost fish and elasmobranchs. Methods We compiled high‐resolution bottom trawl survey data of fish biomass containing 166,000 unique tows and corrected biomass for differences in sampling area and trawl gear catchability. We examined whether relationships between net primary production and demersal fish community biomass are mediated by temperature, food‐web structure and the level of fishing exploitation, as well as the choice of spatial scale of the analysis. Subsequently, we examined if temperature explains regional changes in fish biomass over time under recent warming. Results We find that biomass per km 2 varies 40‐fold across regions and is highest in cold waters and areas with low fishing exploitation. We find no evidence that temperature change has impacted biomass within marine regions over the time period considered. The biomass variation is best explained by an elementary trophodynamic model that accounts for temperature‐dependent trophic efficiency. Main Conclusions Our study supports the hypothesis that temperature is a main driver of large‐scale cross‐regional variation in fish community biomass. The cross‐regional pattern suggests that long‐term impacts of warming will be negative on biomass. These results provide an empirical basis for predicting future changes in fish community biomass and its associated services for human wellbeing that is food provisioning, under global climate change.

Settling of buoyant microplastic in estuaries: The importance of flocculation - Simon Nyboe Laursen; Mikkel Fruergaard; Maya Shakunt Dodhia; Nicole Rita Posth; Maja Bar Rasmussen; Marianne Nylandsted Larsen; Dativa Shilla; Daniel Shilla; Jane James Kilawe; Hellen Joseph Kizenga; Thorbjørn Joest Andersen (Science of The Total Environment, 2023)

Novel transformation strategies improve efficiency up to 10-fold in stramenopile algae - Daniel Poveda-Huertes; Payal Patwari; Jan Günther; Michele Fabris; Johan Andersen-Ranberg (Algal Research, 2023)

Zinc enrichment and isotopic fractionation in a marine habitat of the c. 2.1 Ga Francevillian Group: A signature of zinc utilization by eukaryotes? - Frantz Ossa Ossa; Marie-Laure Pons; Andrey Bekker; Axel Hofmann; Simon W. Poulton; Morten B. Andersen; Andrea Agangi; Daniel Gregory; Christian Reinke; Bernd Steinhilber; Johanna Marin-Carbonne; Ronny Schoenberg (Earth and Planetary Science Letters, 2023)

The role of biochar and zeolite in enhancing nitrogen and phosphorus recovery: A sustainable manure management technology - Chumki Banik; Santanu Bakshi; Daniel S. Andersen; David A. Laird; Ryan G. Smith; Robert C. Brown (Chemical Engineering Journal, 2023)

Local adaptation and spatiotemporal patterns of genetic diversity revealed by repeated sampling of Caenorhabditis elegans across the Hawaiian Islands - Timothy A. Crombie; Paul Battlay; Robyn E. Tanny; Kathryn S. Evans; Claire M. Buchanan; Daniel E. Cook; Clayton M. Dilks; Loraina A. Stinson; Stefan Zdraljevic; Gaotian Zhang; Nicole M. Roberto; Daehan Lee; et al. (Molecular Ecology, 2022)
The nematode Caenorhabditis elegans is among the most widely studied organisms, but relatively little is known about its natural ecology. Genetic diversity is low across much of the globe but high in the Hawaiian Islands and across the Pacific Rim. To characterize the niche and genetic diversity of C. elegans on the Hawaiian Islands and to explore how genetic diversity might be influenced by local adaptation, we repeatedly sampled nematodes over a three‐year period, measured various environmental parameters at each sampling site, and whole‐genome sequenced the C. elegans isolates that we identified. We found that the typical Hawaiian C. elegans niche comprises moderately moist native forests at high elevations (500–1,500 m) where ambient air temperatures are cool (15–20°C). Compared to other Caenorhabditis species found on the Hawaiian Islands ( e.g ., Caenorhabditis briggsae and Caenorhabditis tropicalis ), we found that C. elegans were enriched in native habitats. We measured levels of genetic diversity and differentiation among Hawaiian C. elegans and found evidence of seven genetically distinct groups distributed across the islands. Then, we scanned these genomes for signatures of local adaptation and identified 18 distinct regions that overlap with hyper‐divergent regions, which may be maintained by balancing selection and are enriched for genes related to environmental sensing, xenobiotic detoxification, and pathogen resistance. These results provide strong evidence of local adaptation among Hawaiian C. elegans and contribute to our understanding of the forces that shape genetic diversity on the most remote volcanic archipelago in the world.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Future-proofing hydrogeology by revising groundwater monitoring practice - Gabriel C. Rau; Mark O. Cuthbert; Vincent E. A. Post; Daniel Schweizer; R. Ian Acworth; Martin S. Andersen; Philipp Blum; Elisabetta Carrara; Todd C. Rasmussen; Shemin Ge (Hydrogeology Journal, 2020)
Groundwater is an important global resource and its sustainable use faces major challenges. New methods and advances in computational science could lead to much improved understanding of groundwater processes and subsurface properties. A closer look at current groundwater monitoring practice reveals the need for updates with a special focus on the benefits of high-frequency and high-resolution datasets. To future-proof hydrogeology, this technical note raises awareness about the necessity for improvement, provides initial recommendations and advocates for the development of universal guidelines.

Full lifetime perspectives on the costs and benefits of lay‐date variation in tree swallows - David W. Winkler; Kelly K. Hallinger; Teresa M. Pegan; Conor C. Taff; Mo A. Verhoeven; David Chang van Oordt; Maria Stager; Jennifer J. Uehling; Maren N. Vitousek; Michael J. Andersen; Daniel R. Ardia; Amos Belmaker; et al. (Ecology, 2020)
Animals must balance various costs and benefits when deciding when to breed. The costs and benefits of breeding at different times have received much attention, but most studies have been limited to investigating short‐term season‐to‐season fitness effects. However, breeding early, versus late, in a season may influence lifetime fitness over many years, trading off in complex ways across the breeder’s lifespan. In this study, we examined the complete life histories of 867 female tree swallows ( Tachycineta bicolor ) breeding in Ithaca, New York, between 2002 and 2016. Earlier breeders outperformed later breeders in short‐term measures of reproductive output and offspring quality. Though there were weak indications that females paid long‐term future survival costs for breeding early, lifetime fledgling output was markedly higher overall in early‐breeding birds. Importantly, older females breeding later in the season did not experience compensating life history advantages that suggested an alternative equal‐fitness breeding strategy. Rather, most or all of the swallows appear to be breeding as early as they can, and differences in lay dates appear to be determined primarily by differences in individual quality or condition. Lay date had a significant repeatability across breeding attempts by the same female, and the first lay date of females fledged in our population was strongly influenced by the first lay date of their mothers, indicating the potential for ongoing selection on lay date. By examining performance over the entire lifespan of a large number of individuals, we were able to clarify the relationship between timing of breeding and fitness and gain new insight into the sources of variability in this important life history trait.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Past, Present and Future Eutrophication Status of the Baltic Sea - Ciarán J. Murray; Bärbel Müller-Karulis; Jacob Carstensen; Daniel J. Conley; Bo G. Gustafsson; Jesper H. Andersen (Frontiers in Marine Science, 2019)

Essential ocean variables for global sustained observations of biodiversity and ecosystem changes - Patricia Miloslavich; Nicholas J. Bax; Samantha E. Simmons; Eduardo Klein; Ward Appeltans; Octavio Aburto‐Oropeza; Melissa Andersen Garcia; Sonia D. Batten; Lisandro Benedetti‐Cecchi; David M. Checkley; Sanae Chiba; J. Emmett Duffy; et al. (Global Change Biology, 2018)
Sustained observations of marine biodiversity and ecosystems focused on specific conservation and management problems are needed around the world to effectively mitigate or manage changes resulting from anthropogenic pressures. These observations, while complex and expensive, are required by the international scientific, governance and policy communities to provide baselines against which the effects of human pressures and climate change may be measured and reported, and resources allocated to implement solutions. To identify biological and ecological essential ocean variables ( EOV s) for implementation within a global ocean observing system that is relevant for science, informs society, and technologically feasible, we used a driver‐pressure‐state‐impact‐response ( DPSIR ) model. We (1) examined relevant international agreements to identify societal drivers and pressures on marine resources and ecosystems, (2) evaluated the temporal and spatial scales of variables measured by 100+ observing programs, and (3) analysed the impact and scalability of these variables and how they contribute to address societal and scientific issues. EOV s were related to the status of ecosystem components (phytoplankton and zooplankton biomass and diversity, and abundance and distribution of fish, marine turtles, birds and mammals), and to the extent and health of ecosystems (cover and composition of hard coral, seagrass, mangrove and macroalgal canopy). Benthic invertebrate abundance and distribution and microbe diversity and biomass were identified as emerging EOV s to be developed based on emerging requirements and new technologies. The temporal scale at which any shifts in biological systems will be detected will vary across the EOV s, the properties being monitored and the length of the existing time‐series. Global implementation to deliver useful products will require collaboration of the scientific and policy sectors and a significant commitment to improve human and infrastructure capacity across the globe, including the development of new, more automated observing technologies, and encouraging the application of international standards and best practices.

Forging our understanding of lncRNAs in the brain - Rebecca E. Andersen; Daniel A. Lim (Cell and Tissue Research, 2018)

Design and test of a Microsoft Kinect-based system for delivering adaptive visual feedback to stroke patients during training of upper limb movement - Daniel Simonsen; Mirjana B. Popovic; Erika G. Spaich; Ole Kæseler Andersen (Medical & Biological Engineering & Computing, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Comparison of analytical methods for profiling N- and O-linked glycans from cultured cell lines - Hiromi Ito; Hiroyuki Kaji; Akira Togayachi; Parastoo Azadi; Mayumi Ishihara; Rudolf Geyer; Christina Galuska; Hildegard Geyer; Kazuaki Kakehi; Mitsuhiro Kinoshita; Niclas G. Karlsson; Chunsheng Jin; et al. (Glycoconjugate Journal, 2016)

Height as a prognostic marker for survival during antituberculous therapy - Daniel Faurholt-Jepsen; Nyagosya Range; George Praygod; Kidola Jeremiah; John Changalucha; Åse Bengård Andersen; Henrik Friis (Infectious Diseases, 2015)

Developing tools for defining and establishing pathways of toxicity - Melvin E. Andersen; Patrick D. McMullen; Daniel Krewski (Archives of Toxicology, 2015)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

A free-air system for long-term stable carbon isotope labeling of adult forest trees - Thorsten E. E. Grams; Herbert Werner; Daniel Kuptz; Wilma Ritter; Frank Fleischmann; Christian P. Andersen; Rainer Matyssek (Trees, 2011)

Coastal eutrophication and trend reversal: A Danish case study - Jacob Carstensen; Daniel J. Conley; Jesper H. Andersen; Gunni Ærtebjerg (Limnology and Oceanography, 2006)
In the past 2 decades significant measures have been taken to reduce nitrogen and phosphorus discharges from Denmark by 50% and 80%, respectively. These nutrient reduction targets now appear within reach after several consecutive reduction measures are fully implemented, particularly toward diffuse discharges, and reduced nutrient concentrations are beginning to be observed in estuaries and the Danish straits. Phosphorus concentrations have declined by 22% to 57% from the early 1990s, mainly owing to improved treatment of urban and industrial wastewater. Changes in nitrogen concentrations, following reduction measures toward diffuse sources, were more recent and partly masked by large interannual variations in freshwater discharge. The response in marine nitrogen concentrations was delayed relative to the decline in riverine concentrations, most likely owing to large internal loading from the sediments. Two consecutive dry years appeared to be the triggering mechanism for nitrogen concentrations to decline. In the last 5 yr, nitrogen levels in estuaries and coastal waters have decreased up to 44% when interannual variations in freshwater discharge were accounted for. These first signs of environmental recovery were most pronounced in estuaries and coastal waters but also were apparent in open waters of the Kattegat, the Sound, and the Belt Sea. This case study is the first to document significant decreases in nutrient concentrations on a large regional scale resulting from an active management strategy to reduce nutrients from both diffuse and point sources.

Conservation genetics of harbour porpoises, Phocoena phocoena, in eastern and central North Atlantic - Liselotte Wesley Andersen; Daniel E. Ruzzante; Michael Walton; Per Berggren; Arne Bjørge; Christina Lockyer (Conservation Genetics, 2001)

Contradictory findings in studies of sex ratio variation in roe deer ( Capreolus capreolus ) - A. J. Mark Hewison; Reidar Andersen; Jean-Michel Gaillard; John D. C. Linnell; Daniel Delorme (Behavioral Ecology and Sociobiology, 1999)

Genetic relationship among 19 accessions of six species of Chenopodium L., by Random Amplified Polymorphic DNA fragments (RAPD) - Paulo M. Ruas; Paulo M. Ruas; Alejandro Bonifacio; Alejandro Bonifacio; Claudete F. Ruas; Claudete F. Ruas; Daniel J. Fairbanks; William R. Andersen (Euphytica, 1999)